Identifying idiosyncratic career taste and skill with income risk - Daniel Barth; Stephen H. Shore; Shane T. Jensen (Quantitative Economics, 2017)
How important to well-being is choosing a career with the right fit? We estimate a model of career choice in a setting where we observe the income risk of chosen careers and the risk aversion of the people who choose them. The key parameter of interest representing the importance of idiosyncratic taste and skill in career choice is identified from the shift in the distribution of income risk with risk aversion. We document that those who self-identify as risk tolerant are more likely to have volatile incomes. However, this correlation is far from perfect. The model gives this weak correlation an economic interpretation: idiosyncratic fit is an important determinant of career choice. We separate idiosyncratic career taste from skill using the pay gap between high- and low-income-risk people with high and low risk aversion.
Keywords: J24; 330; Occupational choice; career choice; income risk; idiosyncratic taste and skill